COMMUNITY-BASED ECONOMIC DEVELOPMENT STRATEGY BY UTILIZING TECHNOLOGY AND LOCAL RESOURCES IN THE TUMUMPA VILLAGE COMMUNITY, TUMINTING DISTRICT, MANADO CITY - Jan, Arrazi Hasan; Palandeng, Indrie Debbie; Rogi, Mirah D.G. (Scientica: Jurnal Ilmiah Sains dan Teknologi, 2025)
The purpose of the Community Partnership Program (PKM) is to improve the knowledge and skills of the micro-business community in Tumumpa Village, Tuminting District through a community-based economic development strategy for fishermen in utilizing local technology and resources. The PKM team concluded that the problems faced by this fishing community are limited knowledge and skills in understanding and using technology effectively in their economic efforts and the community faces difficulties in obtaining capital to expand their businesses. To overcome this problem requires a holistic approach involving collaboration between the government, private sector and local communities to ensure that community-based economic development by utilizing local technology and resources can be carried out sustainably and inclusively. The community in the coastal area of ​​Tumumpa Village relies on the fisheries sector for its business. Business actors in this case fishermen have many limitations in utilizing local technology and resources, because the products produced have limitations, namely less creative and innovative. Community-based economic development focuses on fish production which has the potential to improve local economic welfare and sustainability. Through empowering local fishermen, business diversification, use of technology and development of added value, is an approach in community-based economic development and can provide a significant impact in improving community welfare, and promoting long-term economic sustainability. The output plan is an increase in knowledge and skills in utilizing local technology and resources to produce more economical products. The Output Target is a journal published through an ISSN journal and Online Media Publication.